Modeling Calcium Dynamics and Inhibition Based Synaptic Plasticity in Dendritic Spines - Dur-e-Ahmad, Muhammad (Mathematical Modelling and Analysis, 2014)
Inhibitory synapses through GABAergic channels not only change spine’s calcium dynamics but also modulate postsynaptic current mediated through glutamate receptors. However the mechanism and extent to which these inhibitory synapses can modulate postsynaptic potential is not clearly understood. We propose a mathematical model to explain this phenomenon which encompasses both presynaptic and postsynaptic mechanisms. Further this model also elaborates the effect of these channels in synaptic calcium dynamics and learning mechanism.